Evaluasi Tingkat Kualitas Hidup bagi Permukiman Nelayan di Desa Pesisir Tambak Wedi dengan Kriteria Eco-Settlement (EMARA: Indonesian Journal of Architecture, 2016)
As an archipelago, Indonesia has vast expanse of coastal area, that become a prominent source of economic revenue for some communities in Indonesia. Numerous fishing village was formed as a result of economic activity. But unfortunately, the condition of settlements are very dense without orientation to the sustainable environment. The low quality of human resources affect the interpretation of the definition about healthy and livable housing for the community. Research on the quality of life (liveability) of the fishermen settlement area at Tambak Wedi RT.03 RW.02 coastal village in eco-settlement concepts is necessary to investigate the possibility of restructuring the fishing village's settlement into a more livable standards and appropriately the character of the local community. This research using descriptive, evaluative and development methods. The evaluation result about liveability level at Tambak Wedi RT.03 RW.02 coastal village by the eco-settlement criteria, which is consist of ecological, social, economic and institution aspect, show that the settlement is weak in the ecological aspect. Therefore, it is the most possible aspect to be restructured with some actual and simple action, so that the fishermen settlements become liveable and has good quality of life.